Application of Ranque-Hilsh Vortex Tube and Leontiev Tube for Cooling System of Electrical Machines - Tsynaeva A.A.; Tsynaeva E. A. (Problems of the Regional Energetics)
The study was devoted to the development of efficient cooling systems for energy-converting machinery with static energy separators by means of numerical and experimental studies. An experimental study was used for comprehensive analysis of operation regimes of the cooling systems. The experiments were conducted on the test bench. An analysis of operation regime was carried out for two configurations: with and without Ranque-Hilsch energy separators. The study revealed 18-25 % decrease in maximum temperatures of energy-converting machinery when using Ranque-Hilsch separators along with basic heat pipes. Furthermore, Ranque-Hilsch energy separators provided higher temperature drop in the heat pipe. The numerical model was based on the equation of state and conservation equations for mass, energy, and momentum. The numerical study was carried out using the RANS approach with k-omega SST model of turbulence. Free open-source software platform Code_Saturne was used for simulation. The developed numerical model was verified by comparison of the obtained results with adopted experimental data. Additional verification was carried out by comparison with a criterion-oriented calculation of heat exchange. Obtained simulation results showed heat transfer intensification up to 22 % (at a distance of 0-1.45 calibers from the throat of the nozzle) compared to a cylindrical channel. At a distance over 7 calibers, heat transfer efficiency decreases and appears to be up to 24 % lower compared to a cylindrical channel. Based on results of experimental and numerical studies, a potential of increase of energy efficiency of cooling systems for energy-converting machinery when using energy separators has been assessed.